Psychosocial and mental health in cystic fibrosis in the modern era of care: time to evolve - Beth Smith; Tonia A Douglas; Alexandra L Quittner; Anna M Georgiopoulos; Maggie Harrigan (BMJ Open Respiratory Research)
Cystic fibrosis (CF) treatment has revolutionised care over the past three decades with major advances in survival. Despite these advances, CF continues to create psychological and social challenges for people with CF (PWCF) throughout their life and is associated with worse health outcomes and higher healthcare costs. Anxiety and depression screening and management protocols are widely implemented within CF care; however, a much broader scope of psychosocial challenges exist which lack a standardised screening and management approach. The advent of CF transmembrane conductance regulator modulator therapies is transforming the psychosocial landscape for PWCF with new challenges and evolving psychosocial needs. What it means to have CF, the expectations, hopes and stressors are rapidly changing, and psychosocial care must keep pace if health outcomes are to be fully optimised. A symposium of international CF and psychosocial experts was convened in November 2022 to explore current and emerging issues in psychosocial health and identify opportunities and approaches to optimise psychosocial care. This state-of-the-art review summarises key symposium proceedings and highlights priorities for clinical practice and research in psychosocial health across the lifespan among PWCF. It also summarises state-of-the-art initiatives for screening and intervention to optimise CF psychosocial healthcare and patient outcomes.